An agenda for research and action toward diverse and just futures for life on Earth. Issue 4 (3rd March 2021) - Wyborn, C.; Montana, J.; Kalas, N.; Clement, S.; Davila, F.; Knowles, N.; Louder, E.; Balan, M.; Chambers, J.; Christel, L.; Forsyth, T.; Henderson, G.; et al.
Abstract: Decades of research and policy interventions on biodiversity have insufficiently addressed the dual issues of biodiversity degradation and social justice. New approaches are therefore needed. We devised a research and action agenda that calls for a collective task of revisiting biodiversity toward the goal of sustaining diverse and just futures for life on Earth. Revisiting biodiversity involves critically reflecting on past and present research, policy, and practice concerning biodiversity to inspire creative thinking about the future. The agenda was developed through a 2‐year dialogue process that involved close to 300 experts from diverse disciplines and locations. This process was informed by social science insights that show biodiversity research and action is underpinned by choices about how problems are conceptualized. Recognizing knowledge, action, and ethics as inseparable, we synthesized a set of principles that help navigate the task of revisiting biodiversity. The agenda articulates 4 thematic areas for future research. First, researchers need to revisit biodiversity narratives by challenging conceptualizations that exclude diversity and entrench the separation of humans, cultures, economies, and societies from nature. Second, researchers should focus on the relationships between the Anthropocene, biodiversity, and culture by considering humanity and biodiversity as tied together in specific contexts. Third, researchers should focus on nature and economies by better accounting for the interacting structures of economic and financial systems as core drivers of biodiversity loss. Finally, researchers should enable transformative biodiversity research and action by reconfiguring relationships between human and nonhuman communities in and through science, policy, and practice. Revisiting biodiversity necessitates a renewed focus on dialogue among biodiversity communities and beyond that critically reflects on the past to channel research and action toward fostering just and diverse futures for human and nonhuman life on Earth. Abstract : Article Impact Statement : Placing diversity and justice at the heart of transformative change for biodiversity offers important new directions for research and action. Abstract : Una Agenda para la Investigación y la Acción hacia un Futuro Diverso y Justo para la Vida sobre la Tierra Resumen: Las décadas de investigación e intervenciones políticas sobre la biodiversidad han tratado significativamente los temas de la degradación de la biodiversidad y la justicia social. Debido a esto, se requieren nuevas estrategias. Diseñamos una agenda de investigación y acción que llama a la labor colectiva de revisar la biodiversidad hacia el objetivo de sustentar un futuro diverso y justo para la vida sobre la Tierra. Cuando se revisa la biodiversidad, se requiere de una reflexión crítica sobre las investigaciones, políticas y prácticas presentes y pasadas sobre la biodiversidad para inspirar un pensamiento creativo acerca del futuro. Desarrollamos la agenda por medio de un proceso de diálogo de dos años que involucró a casi 300 expertos de diversas disciplinas y localidades. Este proceso estuvo orientado por el conocimiento de las ciencias sociales que muestra cómo la investigación y la acción para la biodiversidad están sostenidas por las opciones de cómo están conceptualizados los problemas. Reconocimos al conocimiento, la acción y la ética como inseparables y sintetizamos un conjunto de principios que ayuda a navegar la labor de revisar la biodiversidad. La agenda articula cuatro áreas temáticas para la investigación en el futuro. Primero, los investigadores necesitan revisar las narrativas de la biodiversidad mediante el cuestionamiento de las conceptualizaciones que excluyen a la diversidad y consolidan la separación entre humanos, culturas, economías y sociedades y la naturaleza. Segundo, los investigadores deberían enfocarse en las relaciones entre el antropoceno, la biodiversidad y la cultura al considerar a la humanidad y la biodiversidad como interconectadas en contextos específicos. Tercero, los investigadores deberían enfocarse en la naturaleza y las economías al tener en mejor cuenta la interacción de las estructuras de los sistemas económico y financiero como conductores nucleares de la pérdida de la biodiversidad. Finalmente, los investigadores deberían permitir la investigación y acción transformadoras de la biodiversidad al reconfigurar las relaciones entre las comunidades humanas y no humanas dentro y a través de la ciencia, la política y la práctica. La revisión de la biodiversidad necesita de un enfoque renovado sobre el diálogo entre las comunidades de la biodiversidad y más allá, que reflexione críticamente sobre el pasado para canalizar a la investigación y acción hacia el fomento del futuro justo y diverso para la vida humana y no humana sobre la Tierra.